Anthropogenic methane plume detection from point sources in the Paris megacity area and characterization of their δ13C signature. (1st February 2020) - Xueref-Remy, I.; Zazzeri, G.; Bréon, F.M.; Vogel, F.; Ciais, P.; Lowry, D.; Nisbet, E.G.
Abstract: Mitigating anthropogenic methane emissions is one of the available tools for reaching the near term objectives of the Paris Agreement. Characterizing the isotopic signature of the methane plumes emitted by these sources is needed to improve the quantification of methane sources at the regional scale. Urbanized and industrialized regions such as the Paris megacity are key places to better characterize anthropogenic methane sources. In this study, we present the results of the first mobile surveys in the Paris region, assessing methane point sources from 10 landfills (which in the regional inventory are the main emission sector of methane in the region), 5 gas storage sites (supplying Paris) and 1 waste water treatment (WWT) facility (Europe's largest, second worldwide). Local atmospheric methane concentration (or mixing ratio) enhancements in the source plumes were quantified and their δ 13 C in CH4 (further noted δ 13 CH4 ) signature characterized. Among the 10 landfills sampled, at 6 of them we detected atmospheric methane local enhancements ranging from 0.8 to 8.5 parts per million (ppm) with δ 13 CH4 signatures between −63.7 ± 0.3 permils (‰) to −58.2 ± 0.3‰. Among the 5 gas storage sites surveyed, we could observe that 3 of them were leaking methane with local methane concentration enhancements ranging from 0.8 to 8.1 ppm and δ 13 CH4 signatures spanning from −43.4 ± 0.5‰ to −33.8 ± 0.4‰. Dutch gas with a δ 13 CH4 signature of −33.8 ± 0.4‰ (typical of thermogenic gas) was also likely identified. The WWT site emitted local methane enhancements up to 4.0 ppm. For this site, two δ 13 CH4 signatures were determined as −51.9 ± 0.2‰ and −55.3 ± 0.1‰, typical of a biogenic origin. About forty methane plumes were also detected in the Paris city, leading to local concentration enhancements whose origin was in two cases interpreted as natural gas leaks thanks to their isotopic composition. However, such enhancements were much less common than in cities of North America. More isotopic surveys are needed to discriminate whether such urban methane enhancements are outcoming from gas line leaks and sewer network emanations. Furthermore, our results lead us to the conclusion that the regional emissions inventory could underestimate methane emissions from the WWT sector. Further campaigns are needed to assess the variability and seasonality of the sources and of their isotopic signature, and to estimate their emissions using methods independent of the inventory. Highlights: CH4 plumes were located on anthropogenic sites in the Paris megacity. A mobile CRDS analyzer was used to detect local methane enhancements in the plume. CRDS and GC-IRMS measurements were performed to provide source isotopic signatures. These results provide independent constraints to quantify regional methane sources.